Development Of Biochemical Struts Model To Improve Water Quality Index Of Industrial Wastewater Treatment Plant With Special Focus On Industrial Heavy Metals (Journal of Pharmaceutical Negative Results, 2023)
As a post-pandemic scenario, communal health issues are studied by many experts throughout the world. Most significant elements of life are air and water. However, as per Indian environmental laws, industries throughout the country are trying to maintain the water contamination level within the acceptable limits. But, in the case of pharmaceutical industries, many times it became difficult to remove the drug byproducts from the water reservoir constructed for water filtrations and after that wastewater is forwarded to nearby rivers if wastewater quality index is within the limit. This wastewater handling cost is more and hence to provide an optimum cost solution this paper presents a new biochemical Struts model which further segregates the different precipitations which can carry heavy metals and can be used for other industrial purposes by recycling water internally instead of draining into rivers/sea, etc.